Migraine - Deza Bringas, Luis (2010)
Migraine is the most frequently reported type of headache. It is characterized as a chronic and episodic neurological disorder associated with vomiting, photophobia, and sonophobia. The occurrence of a migraine headache episode is usually associated with an aura, which is clearly perceived by patients. Migraine headache crises lead to almost total disability in affected patients, so this condition is recognized as a health problem requiring adequate diagnosis and therapy.